Reclaiming Women‟s power by eatery names in two multicultural cities - Ajar Pradika Ananta Tur; Arini Sabrina; Azelin Mohammed Noor; Yashinta Farahsani; Ida Puspita; Muhammad Hafiz Kurniawan (Association for Scientific Computing Electrical and Engineering (ASCEE), 2023)
As patriarchy is not solely based on sexuality, energizing women requires enhancing their intellect and state of mind. It is considered a gesture of respect to refer to a married woman by the name of her husband or eldest son. Women's public participation is still deemed devalued, as evidenced by the naming of restaurants. This study examines eatery names in Yogyakarta, Indonesia, and Malacca, Malaysia, two cities with similar historical backgrounds. It aims to investigate women's efforts to improve their negotiating position in society by naming their eateries. Although two restaurants place women in powerful positions, many still need help to attain women's positions and social respect.